Pemahaman Komprehensif Terhadap Hadis Perintah Memerangi Orang Kafir Antara Hikmah dan Legalitas - Hidayatulah Abdul Rachman; Mohamad Anton Athoillah; Dede Rodlyana; Muhammad Dirman Rasyid (Cakrawala: Journal of Religious Studies and Global Society, 2025)
The Umirtu an uqotila an-naas hadith often draws attention in Islamic legal discourse, sparking profound questions about its meaning in social and legal contexts. This study offers a fresh perspective by combining thematic analysis with an in-depth review of hadith commentary (syarah) and scholarly interpretations. By weighing the wisdom behind the text and its legal implications, the research highlights the importance of understanding this hadith comprehensively and contextually. The findings affirm that narrow interpretations can lead to detrimental misunderstandings, while a balanced approach paves the way for a more relevant and humane application of Islamic law. This article calls readers to delve into the depths of wisdom and legalities, harmonizing the two in addressing the challenges of contemporary Islamic thought.